2018
DOI: 10.22159/ajpcr.2018.v11i7.25477
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Etiology and Antibacterial Resistance Patterns of Dacryocystorhinostomy Cases in the North of Iran S

Abstract: Objective: Nasolacrimal duct obstruction is an annoying medical condition in both ophthalmology and otolaryngology practices. As prophylactic antibiotic therapy decreases the rates of infections, understanding the prompt microbial spectrum of the pathogens has been revealed to be highly effective in such patients. We evaluated the microbial growth and bacterial resistance patterns of Bodkin tube samples obtained from patients who underwent dacryocystorhinostomy (DCR).Methods: A total number of 72 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…among our isolates may be linked to the low socioeconomic profile of the patients and poor hygiene habits. Similarly to our results, Nemati et al 18 and Goel et al 19 reported high rates of enteric floral growth among the gram-negative isolates obtained from silicone tubes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…among our isolates may be linked to the low socioeconomic profile of the patients and poor hygiene habits. Similarly to our results, Nemati et al 18 and Goel et al 19 reported high rates of enteric floral growth among the gram-negative isolates obtained from silicone tubes.…”
Section: Discussionsupporting
confidence: 91%
“…The high prevalence of fungal growth in the studies by Ali et al 12 and Nemati et al 18 might be related to a tropical and moist climate, as the climate is drier in Turkey than South India and the Iranian coast of the Caspian Sea. Increased Enterobacter spp.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations